Inter-relationships between agronomic traits and fruit yield in scarlet eggplant (Solanum aethiopicum (L.) Gilo group). - Ofori, K.; Blay, E.T.; Gamedoagbao, D.K. (Plant Breeding and Seed Science, 2008)
Genotypic correlations and path–coefficients were determined for nine yield-related agronomic traits using 10 accessions of scarlet eggplant. There were significant (p < 0.05) differences among the 10 accessions for all traits and differences were largely due to genetic effects. There was no significant positive correlation of any trait with fruit yield, but number of days to flowering, plant height at flowering and number of days to fruit maturity were significantly (p < 0.05) and negatively correlated with fruit yield. Path-coefficient analyses showed that number of fruits per plant had the highest direct effect on fruit yield, followed by fruit diameter...